Penyuluhan Kesehatan tentang Cuci Tangan dengan Enam Langkah Pada Masyarakat - Mikawati Mikawati; Muh. Zukri Malik; Suriyani Suriyani; I Kade Wijaya; Muaningsih Muaningsih (Idea Pengabdian Masyarakat, 2022)
This Community Service Program (PengMas) is carried out on the villagers of Parang village of Bontoramba Village of South Bontonompo Subdistrict by involving Bontonompo Health Center as the person in charge of the work area that has the target of activities. In general, the purpose of this PKM progran is to increase knowledge about hand washing using good and correct soap with 6 (six steps). A special target is the villagers of Parang village, through this activity the mothers of villagers know how to wash their hands properly with 6 (six) steps. The method used in achieving the goal is counseling with the question and answer lecture method (CTJ) to the target and villagers of Parang village of Bontoramba Village of South Bontonompo Subdistrict. The results of pengmas activities are expected to be in accordance with the targets seen from the active role of citizens during the activity.